Evaluation of Dentistry Undergraduate Students’ General Knowledge Levels and Attitudes About Oral Cancers: A Survey Study - Sena Karacan Çelebi; Elif Polat Balkan (Essentials of Dentistry)
Background: Oral cancers are known to be a major global public health problem, with 377713 new cases and 177757 deaths in 2020. Dentists’ ability to possess sufficient knowledge about oral cancers and recognize premalignant lesions contributes to early diagnosis and treatment. The aim of this study is to measure and evaluate the knowledge, skills, and attitudes of the fourth- and fifth-year students studying at the Faculty of Dentistry concerning oral cancers.